STRATEGI PEMERINTAH TERHADAP PEMBERDAYAAN PEREMPUAN BERBASIS WIRAUSAHA DESA CIPOTAKARI - Ratna Dewi; Erfina Erfina; Monalisa Ibrahim; Sahar Sahar (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2021)
The purpose of this study is to determine the government's strategy for empowering women based on entrepreneurship in Cipotakari village, to determine the factors that influence the government's strategy to empower women based on entrepreneurship in Cipotakari village. The population of this study was 280 people (adult women), while the research sample was 72 people. The data collection techniques used in this study were (1) observation, (2) literature study, and (3) questionnaire. The collected data was then analyzed using a frequency table and using the SPSS 2.1 application. The results of the research on the Government's Strategy for the Empowerment of Entrepreneur-Free Women in Cipotakari Village, Panca Rijang District, can be categorized as